2016
DOI: 10.1016/j.actbio.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

A newly identified mechanism involved in regulation of human mesenchymal stem cells by fibrous substrate stiffness

Abstract: Stiffness of biomaterial substrates plays a critical role in regulation of cell behavior. Although the effect of substrate stiffness on cell behavior has been extensively studied, molecular mechanisms of regulation rather than those involving cytoskeletal activities still remain elusive. In this study, we fabricated aligned ultrafine fibers and treated the fiber with different annealing temperatures to produce fibrous substrates with different stiffness. Human mesenchymal stem cells (hMSCs) were then cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Interestingly, fibrous substrates particularly the 2H group supported endothelial differentiation of MSCs more effectively than polystyrene culture plates. We also found that the expression level of MIF , a chemokine regulated by tissue stiffness and culture stiffness, showed the same trend with that of CD31, vWF, or VEGF , suggesting that MIF may be involved in the regulation of differentiation from MSCs to ELCs.…”
Section: Resultssupporting
confidence: 57%
“…Interestingly, fibrous substrates particularly the 2H group supported endothelial differentiation of MSCs more effectively than polystyrene culture plates. We also found that the expression level of MIF , a chemokine regulated by tissue stiffness and culture stiffness, showed the same trend with that of CD31, vWF, or VEGF , suggesting that MIF may be involved in the regulation of differentiation from MSCs to ELCs.…”
Section: Resultssupporting
confidence: 57%
“…Substrate stiffness dictates hMSC differentiation through the MIF-mediated AKT/YAP/RUNX2 pathway. Once a stem cell contacts a stiffer substrate, intracellular migration inhibitory factor (MIF) increases and starts a pathway towards AKT/YAP signaling inside the nucleus which promotes osteogenic development (Figure 7) [96]. Other regulation mechanisms such as the p190RhoGAP pathway have been characterized proving the intricacies and intertwining intracellular signaling that occurs once a cell comes into contact with a substrate with certain rigidity.…”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…The relevance of YAP/vinculin activity on the osteogenic effect of progenitor cells has been reported. 40,41 As osteogenic markers, Runt-related transcription factor 2 (RUNX2) and osteocalcin (OCN) were potentially affected by multiple pathways, such as integrin and stiffness-related vinculin/YAP pathways in the current scenario. Therefore, in order to access the general osteogenic effect of different scaffolds, western blot was performed to compare the expression level of RUNX2 and OCN in BMSCs seeded on different scaffolds for 7 days in osteogenic medium.…”
Section: Resultsmentioning
confidence: 99%